ACEH SERAMBI MEKKAH (Studi tentang Peran Ibadah Haji dalam Pengembangan Peradaban Aceh) - Saifuddin Dhuhri (Islam Futura, 2017)
Great scholars with great number of literature have previously discussed the legacy of the Islamic pilgrimage's role in spreading Islam as the Acehnese identity. However, few references extrapolate the role of Islamic pilgrimage as the mechanism of Acehnese identity formulation. Based on observation of the current site of Rumoh Aceh in Mecca, and extensive reading on Acehnese heritage, I argue that the Islamic pilgrimage (Hajj) played an extremely important role in developing Acehnese civilisation, as it might have worked as the mechanism of creating Acehnese identity among the Southeast Asian neighbours. This article concentrates on the pilgers' route of Malacca straits' role before the invention of steam machine and during the heyday of Acehnese civilisation. This works has significant contribution to raise the awareness of the fact that is believed to be the strong reason why the Acehnese civilisation has become the leading power at that time.